Design of New Student Registration System Using Web-Based Waterfall Method - Yusma, Yanti; Rizal, Chairul; Ziky, Ziky (SAINTEKBU, 2025)
New student admission is one of the crucial processes in educational institutions that require accurate and efficient data management. MTs Amaliyah Sunggal, located at Jl. Tani Asli, Kp. Lalang, Kec. Sunggal, Deli Serdang Regency, North Sumatra, previously implemented a manual registration system that had many obstacles, such as a long process, data recording errors, and difficulty in monitoring registration progress. To overcome these obstacles, a web-based new student registration system was designed using the Waterfall development method. The Waterfall method was chosen because it has a systematic and orderly structure, which includes five main stages, namely needs analysis, system design, implementation, testing, and maintenance. In the design process, user needs are identified in detail to ensure that the system can accommodate all required functions. After that, the system is designed and implemented using web technology that allows prospective students to register online, thereby reducing the school's administrative burden. This system has been tested using Lighthouse which showed quite good performance with First Contentful Paint (FCP) of 1.6 seconds and Largest Contentful Paint (LCP) of 2.6 seconds, while Total Blocking Time (TBT) and Cumulative Layout Shift (CLS) obtained perfect scores reflecting the stability of the layout and speed of the system. This system provides convenience for prospective students to access registration information from anywhere and at any time. In addition, the school can monitor registration data in real-time and generate reports automatically. Thus, it is expected that this system can improve efficiency, accuracy, and transparency in the process of accepting new students at MTs Amaliyah Sunggal.